Pengaruh Rata-rata Pengeluaran Perkapita, Indeks Kebahagiaan dan Usia Kawin Pertama terhadap Fertility Rate Di Indonesia (Jurnal Ekonomi Pembangunan Widya Mandira, 2025)
This study aims to examine the effect of average per capita expenditure, happiness index, and age at first marriage on the Total Fertility Rate (TFR) in Indonesia. The main issue addressed is the variation in fertility levels among provinces, which is presumed to be influenced by these three variables. The research utilized secondary cross-sectional data from all provinces in 2021, obtained from the Indonesian Central Statistics Agency (BPS). Data were collected through documentation, and the analysis was carried out using multiple linear regression. The findings reveal that average per capita expenditure has a significant negative effect on TFR (t = –2.177 > t-table 1.697; p = 0.037 < 0.05). Meanwhile, the happiness index (t = 0.946; p = 0.351) and age at first marriage (t = 0.652; p = 0.519) show no significant impact on TFR. Further analysis indicates that per capita expenditure does not significantly influence the happiness index (t = –0.433; p = 0.668), and age at first marriage also has no significant effect on happiness (t = 1.539; p = 0.134). Jointly, the three independent variables do not have a significant effect on TFR in Indonesia (F = 1.779 < F-table 2.93; p = 0.172).
Keywords: Fertility; Per Capita Expenditure; Happiness Index; Age at First Marriage.